1999
DOI: 10.1073/pnas.96.22.12412
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the proximal heme thiolate ligand in chloroperoxidase with a histidine residue

Abstract: Chloroperoxidase is a versatile heme enzyme which can cross over the catalytic boundaries of other oxidative hemoproteins and perform multiple functions. Chloroperoxidase, in addition to catalyzing classical peroxidative reactions, also acts as a P450 cytochrome and a potent catalase. The multiple functions of chloroperoxidase must be derived from its unique active site structure. Chloroperoxidase possesses a proximal cysteine thiolate heme iron ligand analogous to the P450 cytochromes; however, unlike the P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 60 publications
4
64
1
2
Order By: Relevance
“…Recently it has been found that these mechanisms may not be entirely valid, and the actual mechanism may involve two electrophilic oxidants and/or two spin states of the iron oxo species (6,8,14). Although P450cam has been shown to lose its hydroxylation activity when an imidizole is substituted for the axial thiolate ligand (15,16), in contrast, chloroperoxidase retains its chlorination, peroxidation, epoxidation, and catalase activities when its thiolate ligand is mutated to histidine (17). Also, studies with iron porphyrin compounds have demonstrated that imidazole ligation can replace the thiolate in P450 type reactions under certain conditions (18).…”
Section: Myoglobin (Mb)mentioning
confidence: 99%
“…Recently it has been found that these mechanisms may not be entirely valid, and the actual mechanism may involve two electrophilic oxidants and/or two spin states of the iron oxo species (6,8,14). Although P450cam has been shown to lose its hydroxylation activity when an imidizole is substituted for the axial thiolate ligand (15,16), in contrast, chloroperoxidase retains its chlorination, peroxidation, epoxidation, and catalase activities when its thiolate ligand is mutated to histidine (17). Also, studies with iron porphyrin compounds have demonstrated that imidazole ligation can replace the thiolate in P450 type reactions under certain conditions (18).…”
Section: Myoglobin (Mb)mentioning
confidence: 99%
“…Our similar studies with CPO mutants indicated that the thiolate ligand (Cys 29 ) could be replaced with a histidine residue and retain most of the chlorination, peroxidation, epoxidation, and catalase activities (68). C. fumago, the fungus that produces wild-type CPO, was used for the expression of the Cys-to-His mutant.…”
Section: Active-site Mutants Of Cpomentioning
confidence: 75%
“…However, in contrast to the results of P450cam C357H, the thiolate coordination in chloroperoxidase is suggested to be not as important as in P450. After substituting the proximal thiolate ligand (Cys 29) with a histidine, the CPO C29H was found to retain most (around 80%) of its chlorination, peroxidation, epoxidation and catalase activities compared to those of the wild type protein (114). These are surprising observations in consideration of many suggestions for the significance of the proximal thiolate ligand in P450.…”
Section: Cpo C29h and Cpo E183hmentioning
confidence: 92%
“…Glu183 then protonates the distal oxygen of Cpd 0 and the peroxide O-O is cleaved heterolytically to generate Cpd I and release a water molecule, similar to other peroxidase mechanisms (107,108). CPO is adept in catalyzing a number of chiral oxidations with high yields and high enantioselectivity, in addition to alkyne hydroxylation and heteroatom dealkylation (109)(110)(111)(112)(113)(114). The stereoselective ability of CPO in catalysis is suggested to be based on its unique active site structure and unique catalytic mechanism, which make it the promising candidate for industrial catalysts.…”
Section: Chloroperoxidase: a P450-peroxidase Hybridmentioning
confidence: 99%